A Co-creation Centre for Accessible Rehabilitation Technology - Kerr, Andy; Grealy, Madeleine Ann; Kuschmann, Anja; Rutherford, Rosie; Rowe, Philip (Frontiers in Rehabilitation Sciences, 2022)
Background: The prevalence of disabling conditions is increasing globally. Rehabilitation improves function and quality of life across many conditions, particularly when applied intensively. The limited workforce, however, cannot deliver evidence-based intensive rehabilitation. By providing individuals with the tools for self- rehabilitation, technology helps bridge the gap between evidence and practise. Few people, however, can access rehabilitation technology. Barriers such as cost, training, education, portability and poor design stand in the way of equitable access. Our group of engineers and researchers have established a centre dedicated to developing accessible technology through close, frequent engagement with users and industry. Methods: The centre employs a co-creation model, coupling engineering and science with user experience and industrial partnerships to develop accessible technology and associated processes. Due to the complexity and size of the challenge the initial focus is stroke. Recruited through a medical charity, participants, with a wide range of disabilities, use prototype and commercial technology during an 8-week rehabilitation programme with supervision from health professionals. The centre includes de-weighting systems, neurostimulation, virtual reality, treadmills, bespoke rehab games, communication apps, powered exercise equipment and gamified resistance equipment. Standard outcome measures (International Classification of Functioning, Disability and Health) are recorded before, during, immediately after, and 3 months after the intervention and used in combination with an interview to design the initial rehabilitation programme, which is reviewed fortnightly. Qualitative methods (surveys and interviews) are used to capture personal experiences of the programme and individual technology and an advisory group of stroke survivors help interpret outcomes to feed into the technology design process. Ethical approval has been granted for a pilot cohort study with stroke survivors, which is currently underway (01/09/2021–31/12/2021) investigating acceptability and feasibility, due to report findings in 2022. Discussion: Through partnerships, research collaborations and a co-creation model a new centre dedicated to the development of accessible rehabilitation technology has been launched and currently undergoing acceptability and feasibility testing with stroke survivors. The centre, through its close engagement with users and industry, has the potential to transform the way rehabilitation technology is developed and help revolutionise the way rehabilitation is delivered.